2018
DOI: 10.1007/s11626-018-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Nacre formation by epithelial cell cultures from mantle of the black-lip pearl oyster, Pinctada margaritifera

Abstract: Mantle tissue from the black-lip pearl oyster, Pinctada margaritifera, was cultured in vitro using sterilized seawater supplemented with 0.1% yeast extract as the culture medium. Granular and agranular epithelial cells, hyalinocytes, and fibroblast-like cells were observed in the initial stages of culture. Epithelial cells later formed pseudopodial cell networks containing clusters of granulated cells, which upon maturation released their colored granules. These granules induced formation of nacre crystal depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…Results of gene expression studies of the mantle cell cultures were in agreement with that in the mantle tissue, which demonstrated that in vitro cultured mantle epithelial cells could synthesize shell matrix proteins similar to the mantle epithelia in vivo. The amplification results of nacrein are in accordance with previous reports in P. fucata by Gong et al (2008) and in P. margaritifera by Jayasankar et al (2018). Gong et al (2008) reported the expression of nacrein in mantle cell cultures of P. fucata.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Results of gene expression studies of the mantle cell cultures were in agreement with that in the mantle tissue, which demonstrated that in vitro cultured mantle epithelial cells could synthesize shell matrix proteins similar to the mantle epithelia in vivo. The amplification results of nacrein are in accordance with previous reports in P. fucata by Gong et al (2008) and in P. margaritifera by Jayasankar et al (2018). Gong et al (2008) reported the expression of nacrein in mantle cell cultures of P. fucata.…”
Section: Discussionsupporting
confidence: 91%
“…Cultures with a mixture of epithelial cells, hyalinocytes, hemocytes and other cell types as previously reported for P. fucata (Dharmaraj and Suja, 2002, 2006Suja and Lakshmana Senthil, 2019), abalone mantle cells (Auzoux-Bordenave et al 2007;O'Neill et al, 2013;Suja 2003;Suja and Dharmaraj, 2005) and P. margaritifera (Jayasankar et al, 2018) were obtained from mantle explants. Morphology and cellular behaviour similar to that described in the previous cell cultures were confirmed during this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations